Mesoporous Carbon Nanofibers Embedded with MoS2 Nanocrystals for Extraordinary Li‐Ion Storage. Issue 50 (30th October 2015) - Hu, Shan; Chen, Wen; Uchaker, Evan; Zhou, Jing; Cao, Guozhong
Abstract: MoS2 nanocrystals embedded in mesoporous carbon nanofibers are synthesized through an electrospinning process followed by calcination. The resultant nanofibers are 100–150 nm in diameter and constructed from MoS2 nanocrystals with a lateral diameter of around 7 nm with specific surface areas of 135.9 m 2  g −1 . The MoS2 @C nanofibers are treated at 450 °C in H2 and comparison samples annealed at 800 °C in N2 . The heat treatments are designed to achieve good crystallinity and desired mesoporous microstructure, resulting in enhanced electrochemical performance. The small amount of oxygen in the nanofibers annealed in H2 contributes to obtaining a lower internal resistance, and thus, improving the conductivity. The results show that the nanofibers obtained at 450 °C in H2 deliver an extraordinary capacity of 1022 mA h g −1 and improved cyclic stability, with only 2.3 % capacity loss after 165 cycles at a current density of 100 mA g −1, as well as an outstanding rate capability. The greatly improved kinetics and cycling stability of the mesoporous MoS2 @C nanofibers can be attributed to the crosslinked conductive carbon nanofibers, the large specific surface area, the good crystallinity of MoS2, and the robust mesoporous microstructure. The resulting nanofiber electrodes, with short mass‐ and charge‐transport pathways, improved electrical conductivity, and large contact area exposed to electrolyte, permitting fast diffusional flux of Li ions, explains the improved kinetics of the interfacial charge‐transfer reaction and the diffusivity of the MoS2 @C mesoporous nanofibers. It is believed that the integration of MoS2 nanocrystals and mesoporous carbon nanofibers may have a synergistic effect, giving a promising anode, and widening the applicability range into high performance and mass production in the Li‐ion battery market. Abstract : High‐performance anodes : Mesoporous carbon nanofibers embedded with MoS2 nanocrystals through a facile electrospinning method exhibit an improved capability of 1022 mA h g −1 and an improved cycling stability, with only 2.3 % capacity loss after 165 cycles at a current density of 100 mA g −1, as well as a good cyclic stability. Different heat treatments are assessed to achieve good crystallinity and the desired mesoporous microstructure, resulting in an enhanced electrochemical performance.